Penatalaksanaan Fisioterapi Pada Kasus PostOrif Fraktur Intertrochantor Femur SinistraDi RS Ortopedi Dr. R. Soeharso Surakarta - Hardani, Siti, Wijianto,SST.FT.,M.Or (2016)
Background: Fracture intertrochantor femur is break continuity of femur bone between trochantor major and trochantor minor that can cause pain, oedem, limitatied range of motion, decrease muscle strength and limited in functional activities. This case can manage by physiotherapy modality. Physiotherapy modalities used in this case is theraputic exercise like isometrik exercise, active movement and gait exercise. Purpose: To study about physiotherapy management in reducing pain, reduce oedema, increase range of motion, increase muscle strength and increase functional aktivities using modalities isometrik exercise, active movement and gait exercise. Result: After terapy about four times the obtain result of the assessment of motionless pain T0: 4,2 to T4: 1,9; pressure pain T0: 6,3 to 3,7 and motion pain T0: 7,6 to T4: 5,6. Reduce oedem ankle T0: 6 cm to T4: 1 cm. Increase active renge of motion hip joint T0: S : 00-0-00 to T4: S: 200-0-650 , frontal plane T0: 00- 0-00 to T4: 100-0-350. Increase muscle strength of hip fleksor T0:1 to T4: 4, ekstensor, abduktor and adduktor hip from T0: 1 to T4: 3. Increase of functional activities from T0: 0% to 8,75%. Conclution: Isometrik exercise, active exercie and gait exercise can reducing pain, reduce oedema, increase range of motion, increase muscle strength and increase functional aktivities. Keywords: Fracture intertrochantor, isometrik exercise, active movement and gait exercise.